التدريس الفعال وفق نظرية القبعات الست في التفكير - بن عرعور, بلال; بن زروال, فتيحة; بلقيدوم, بلقاسم (جامعة الوادي University of Eloued, 2018)
تسعى هذه الدراسة إلى تبيان أهمية نظرية القبعات الست في التفكير في مجال التدريس، وذلك من خلال شرح مفاهيمها الأساسية، وتبيان أهمية اعتمادها في مجال التدريس من خلال ما أثبتته الدراسات العلمية بخصوص أثرها في مختلف جوانب الأداء الأكاديمي للمتعلمين. وتكمن قيمة نظرية القبعات الست في التفكير في تحقيق المبادئ الأساسية للتدريس الفعال من تخطيط، وإعداد وترجمة لمحتوى المقررات الدراسية في شكل أنشطة، وإدارة التعلم من طرف المتعلم، وتقييم، إضافة إلى أنها تعمل على جعل التلميذ قادرا على المشاركة والتفاعل الصفي، وتنمي مهارات تفكيره وقدرته على اجتياز التعقيدات والصعوبات ومواجهة المشكلات؛ فسوف يتم اقتراح نموذج خطة تدريسية وفق هذه النظرية تعالج من خلالها نقاط الضعف في الخطط المعمول بها.ABSTRACT: This study aims to demonstrate the importance of Edward De Bono's Six Thinking Hats Theory in teaching. First by explaining its basic concepts; then demonstrating the benefit of its use in teaching, through what different studies have proven about its impact on various aspects of learners’ academic performance. And since the Six Thinking Hats Theory value lies in realizing effective teaching basic principles including: planning, preparation, converting curriculum’s contents into activities, self management learning, and assessment; in addition to make sure learners participate and interact in class, develop his/her thinking skills and ability to overcome complexities and difficulties, and solve problems. A model of a teaching plan will be proposed according to this theory, which will address weaknesses in the existing plans.
مقال
Keywords: نظرية قبعات التفكير الست؛ التفكير؛ التدريس الفعال; Six Thinking Hats Theory; thinking; Edward De Bono; effective teaching